2017
DOI: 10.1111/jace.15201
|View full text |Cite
|
Sign up to set email alerts
|

Titanium diboride–silicon carbide–boron carbide ceramics with super‐high hardness and strength

Abstract: Triplex particulate composites composed of boride and carbide ceramics were found to have high strength, hardness, and fracture toughness values. Two compositions consisting of 70:15:15 and 1:1:1 volume ratios of TiB2, SiC, and B4C were produced from commercially available powders by hot‐pressing. The 70:15:15 ceramic exhibited a strength of ~1.3 GPa, while the 1:1:1 ceramic had a strength of ~0.9 GPa. These strengths are comparable to super‐strong Y2O3‐PSZ and β‐SiAlON based composites. The Vickers’ hardness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Diborides (TMB 2 ) and transition metal tetraborides (TMB 4 ) have been widely investigated over the last years . However, the reported Vickers hardness of TMB 2 or TMB 4 is difficult to meet the requirement of superhard material . Naturally, the Vickers hardness of TMBs mainly relies on the shorter and network covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Diborides (TMB 2 ) and transition metal tetraborides (TMB 4 ) have been widely investigated over the last years . However, the reported Vickers hardness of TMB 2 or TMB 4 is difficult to meet the requirement of superhard material . Naturally, the Vickers hardness of TMBs mainly relies on the shorter and network covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…7,11 The relative density of B 4 C-TiB 2 showed a decreasing tendency as the content of TiB 2 increased. 5,7,[12][13] As a consequence, the sintering additive was further introduced to improve the densification of B 4 C-TiB 2 system, including metallic addition, [14][15][16] oxides, [17][18] carbides, [19][20][21][22][23] borides, 24 etc. The addition of Mo and other metals, such as Fe, Co, and Ni, is favorable to form the liquid phase during sintering and thus improve the densification and mechanical properties of TiB 2 -based ceramics.…”
mentioning
confidence: 99%
“…3,8,9,14 Typically, these materials have been produced by hot pressing or spark plasma sintering of mixtures of a primary TM compound (e.g., ZrB 2 ) with a compound containing a second TM such as Mo, Ta, or W. Most reported diborides with core-shell microstructures also contain a source of silicon, such as SiC or a TM disilicide. 10,[15][16][17] Formation of the core-shell microstructure has been attributed to a transient liquid phase that forms due to the reaction of Si with residual surface oxides. 8,18,19 However, some studies have demonstrated the formation of core-shell materials in systems that do not contain Si, such as TiB 2 -WC and ZrB 2 -W, although core-shell formation was still attributed to liquid phase processes.…”
Section: Introductionmentioning
confidence: 99%
“…In core–shell microstructures, the solid solution shells can contain from 3 to 20 at% or more of the second TM 3,8,9,14 . Typically, these materials have been produced by hot pressing or spark plasma sintering of mixtures of a primary TM compound (e.g., ZrB 2 ) with a compound containing a second TM such as Mo, Ta, or W. Most reported diborides with core–shell microstructures also contain a source of silicon, such as SiC or a TM disilicide 10,15–17 …”
Section: Introductionmentioning
confidence: 99%